. Logging during diamond drilling?: Autonomous logging integrated into the Bottom Hole Assembly - Greenwood, A.; Kepic, Anton; Podolska, A.; Dupuis, C.; Stewart, G. (Australian Society of Exploration Geophysicists, 2015)
Logging total count gamma data while diamond drilling an HQ borehole has been achieved using an autonomous shuttle. The shuttle is integrated into the Bottom Hole Assembly (BHA) prior to drilling. Logging is initiated at the beginning of each core run and the shuttle unit continuously logs at 1 second intervals. Continuous logging combined with the relatively slow rate of penetration of diamond drilling results in high fidelity logs at 1-5 cm intervals. The data is collected by the drilling crew, who download and email the data at the end of each core run for near real time analysis. Little to no interruption to the normal drilling process is experienced once the Shuttle has been integrated into the BHA. Autonomous logging while diamond drilling enables the collection of in-situ rock property measurements, without the risks and costs associated with later wireline logging. This value is added to the drilling process at little expense.